Effects of enzyme + bacteria treatment on growth performance, rumen bacterial diversity, KEGG pathways, and the CAZy spectrum of Tan sheep. Issue 1 (1st January 2020) - Jiang, Biwei; Wang, Tian; Zhou, Yuxiang; Li, Fei
ABSTRACT: In this study, the effects of enzyme +bacteria treatment of buckwheat straw and alfalfa on growth performance and rumen bacterial diversity was investigated, 20 three-month-old Ningxia Tan sheep with similar body weights were selected and randomly divided into two groups, 10 sheep in each group. The control group was fed with basal diet + untreated buckwheat straw and alfalfa (the ratio of buckwheat to alfalfa was 2:8), and the experimental group was fed with basic diet + cellulase (enzyme activity ≥ 10, 000 U/g) + compound probiotics (enzyme to bacteria ratio 8:20). 1) The total weight gain and average daily gain of Tan sheep in the experimental group were extremely significantly higher than those in the control group ( P < 0.01). 2). The proportion of Firmicutes in the experimental group was significantly higher than that in the control group ( P < 0.05). 3). In the KEGG pathway B level, 15 genes were significantly higher than in the control group ( P < 0.05). 4). In the CAZy level B, 12 genes were upregulated in the experimental group compared with the control group ( P < 0.05), 3 genes were downregulated ( P < 0.05).Feeding Tan sheep with buckwheat straw and alfalfa treated with enzyme and bacteria can improve the weight gain effect, change the rumen bacterial diversity, and increase the some functional genes in the rumen. The conditions of this experiment would be beneficial to the healthy breeding of Tan sheep, and thus the methods can be used in commercial production. Graphical abstract: